An Analytical model of a radially magnetised longitudinal-flux permanent magnet air-cored linear oscillatory machine - Chembe, Dickson Kanungwe (Stellenbosch : Stellenbosch University, 2019)
Thesis (PhD)--Stellenbosch University, 2019.